Comparative analysis of antioxidant effects of melatonin and vitamin E on H2O2-generated lipid peroxides in tissue homogenates - Baydas, Giyasettin; Canatan, Halit (My University, 2001)
Living organisms developed a comprehensive array of antioxidant defence systems during the evolution to reduce and/or prevent free radical formation or limit their damaging effects. Melatonin and vitamin E are among the most important natural antioxidants. In the present work we extend observations on protective effects of these two antioxidants in an in vitro system to understand their role(s) in various tissues. For this purpose rat tissues were homogenized and incubated with various concentrations of H2O2. To these mixtures, melatonin and vitamin E were added in different concentrations. Subsequently, levels of formed malondialdehyde (MDA) were measured. Our results show that MDA levels were lower in tissue homogenates (especially in brain) supplied by melatonin compared to vitamin E. Therefore, it is possible to postulate that melatonin has more powerful and effective antioxidant role than vitamin E has.
Keywords: Animalia; alpha tocopherol; free radical; hydrogen peroxide; lipid peroxide; malonaldehyde; melatonin; animal tissue; antioxidant activity; article; brain tissue; concentration response; drug mechanism; evolution; in vitro study; male; nonhuman; rat; tissue homogenate